Interpersonal projection as EFL teachers' discourse strategy to enhance students' willingness to communicate: A systemic-functional perspective. (February 2022) - Yang, Xueyan; Yin, Shunli
Abstract: Previous studies have revealed situational variables affecting the moment-by-moment state of students' willingness to communicate (WTC), but few have addressed teachers' strategies enhancing students' WTC, which are highly required in contexts of EFL teaching where low WTC has been noted. This study explores the extent to which interpersonal projection (IP)—a meaning-making resource used to invite the addressee to express a personal viewpoint—can be used by EFL teachers as a discourse strategy to enhance students' WTC. An experiment was conducted in which students at two different levels of English proficiency answered teacher questions in two forms, one with IP added and the other without. A follow-up semi-structured interview with EFL teachers elicited their perceptions on IP's role in teacher-student communication. Results indicated that the questions added with IP were significantly associated with higher WTC as manifested in lengthier and more complex student answers, despite differences in students' levels of English proficiency or the types of questions asked; and that the teachers perceived IP as helpful in reducing teacher-student distance and promoting student thinking and speech production. The findings are discussed in relation to both pedagogical practices and WTC research. Highlights: A systemic-functional approach to teacher discourse in classroom communication. Teacher discourse as a predictor of students' willingness to communicate (WTC). Quantitative and qualitative analysis of data from an experiment and interview. Interpersonal projection in teacher discourse significantly related to high WTC. Interpersonal projection as teachers' discourse strategy to enhance students' WTC.